nPCA: a linear dimensionality reduction method using a multilayer perceptron - Li, Juzeng; Wang, Yi (Frontiers in Genetics, 2024)
Linear dimensionality reduction techniques are widely used in many applications. The goal of dimensionality reduction is to eliminate the noise of data and extract the main features of data. Several dimension reduction methods have been developed, such as linear-based principal component analysis (PCA), nonlinear-based t-distributed stochastic neighbor embedding (t-SNE), and deep-learning-based autoencoder (AE). However, PCA only finds the projection direction with the highest variance, t-SNE is sometimes only suitable for visualization, AE and nonlinear methods discard the linear projection.To retain the linear projection of raw data and generate a better result of dimension reduction either for visualization or downstream analysis, we present neural Principal Component Analysis (nPCA), an unsupervised deep learning approach capable of retaining richer information of raw data as a promising improvement to the PCA. To evaluate the performance of the nPCA algorithm, we compare the performance of both 10 public datasets and 6 single-cell RNA sequencing (scRNA-seq) datasets of the pancreas, benchmarking our method with other classic linear dimensionality reduction methods.We concluded that the nPCA method is a competitive alternative method for dimensionality reduction tasks.